Efficacy of neoadjuvant and adjuvant chemotherapy for localized and locally advanced upper tract urothelial carcinoma: a systematic review and meta-analysis - Quhal, Fahad; Mori, Keiichiro; Sari Motlagh, Reza; Laukhtina, Ekaterina; Pradere, Benjamin; Rouprêt, Morgan; Necchi, Andrea; Moschini, Marco; Shariat, Shahrokh F (International journal of clinical oncology, 2020)
The objectives of this study are to evaluate the available literature regarding the oncologic effect of neoadjuvant and adjuvant chemotherapy in the treatment of patients with clinically non-metastatic upper tract urothelial carcinoma (UTUC) and locally advanced UTUC. We searched PubMed, Cochrane Library, and Scopus databases in November 2019, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. We included studies that compared patients with non-metastatic UTUC who received either neoadjuvant or adjuvant chemotherapy with patients who underwent surgery alone. Subgroup meta-analyses were also performed for studies that investigated only locally advanced UTUC. Overall, 36 studies were included in the review of which 22 studies and 15,378 patients were eligible for the meta-analysis. Neoadjuvant chemotherapy (NAC) was associated with higher rates of pathological downstaging (pDS) (RR 6.48, 95% CI 2.05-20.44, p = 0.001) and pathological complete response (RR 18.46, 95% CI 3.34-99.24, p = 0.001); and this was also proven in a subgroup analysis of studies that evaluated pDS in locally advanced UTUC (RR 3.18, 95% CI 2.0-5.07, p < 0.001). The association of NAC with overall survival (OS) and cancer-specific survival (CSS) was also statistically significant in all patients and in patients with locally advanced UTUC. Adjuvant chemotherapy (AC) was associated with improved metastasis-free survival (HR 0.65, 95% CI 0.55-0.76, p < 0.001) and CSS (HR 0.66, 95% CI 0.57-0.77, p < 0.001), which continued to be true for the patients with locally advanced UTUC. The association of AC with OS was only significant in patients with locally advanced UTUC. Perioperative chemotherapy might provide better survival outcomes in patients with clinically non-metastatic UTUC treated with radical nephroureterectomy. Neoadjuvant chemotherapy seems to have promising results, although high level of evidence is still lacking. Despite the low level, the body of evidence suggests a need for multimodal therapy of invasive UTUC.
Keywords: výsledek terapie; neoadjuvantní terapie; Nephroureterectomy; Chemotherapy; Treatment Outcome; adjuvantní chemoterapie; nefroureterektomie; Adjuvant; Neoadjuvant Therapy; Urologic Neoplasms; lidé; urologické nádory; Neoadjuvant; Chemotherapy, Adjuvant; Humans; karcinom z přechodných buněk; Carcinoma, Transitional Cell; Upper urinary tract urothelial carcinoma